2018
DOI: 10.1111/vox.12666
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of allogenic red cells: benefits and risks

Abstract: Transfusion of rejuvenated red cells reduces organ injury attributable to the red cell storage lesion without adverse effects in experimental studies in vivo. The clinical benefits of this intervention remain uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Rejuvenation did not alter antigenicity, and no bacterial contamination was detected in units rejuvenated during laboratory or operational phases. These changes were qualitatively and quantitatively similar to the results of RBC rejuvenation reported previously . Using the laboratory and early operational findings to set a trial component specification of key quality assurance metrics, RBCs then rejuvenated during an operational validation in a UK blood processing center were found to be compliant.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Rejuvenation did not alter antigenicity, and no bacterial contamination was detected in units rejuvenated during laboratory or operational phases. These changes were qualitatively and quantitatively similar to the results of RBC rejuvenation reported previously . Using the laboratory and early operational findings to set a trial component specification of key quality assurance metrics, RBCs then rejuvenated during an operational validation in a UK blood processing center were found to be compliant.…”
Section: Discussionsupporting
confidence: 77%
“…The manufacturing process for RBC rejuvenation described here results in units that reproducibly meet a specification comparable to that in previous clinical and experimental studies where rejuvenated RBCs have been shown to be safe and effective. RBCs with these properties following rejuvenation have been shown to have superior oxygen delivery and homeostatic and anti‐inflammatory effects relative to standard stored RBCs in experimental studies, as well as in limited clinical evaluations . In addition, key quality parameters for rejuvenation including ATP and 2,3 DPG were maintained to levels equivalent or superior to standard care units for at least 24 hours regardless of the age of units before rejuvenation.…”
Section: Discussionmentioning
confidence: 99%
“…This causes the activation of the phosphatase three enzyme, which degrades 2,3-DPG, due to which the oxygen affinity of hemoglobin is increased, and less oxygen is transferred to tissue from the lungs by RBC (Bellelli and Brunori, 2020). Study shows that essentially no 2,3-DPG will remain after 21 days of storage in CPD and CPDA-1 (Aujla et al, 2018).…”
Section: Fig02mentioning
confidence: 99%
“…Some of the most studied new strategies include the use of different additive solutions other than the commonly used [19] . For example, stored units can be added, with rejuvenating solutions containing pyruvate, inosine, phosphate, and adenine [51] or alkaline additives [41] , which, in metabolomics studies conducted by Gehrke et al [52] and D’Alessandro et al [53] , respectively, were found to be effective in restoring the energy and redox metabolism of RBCs. Another possible strategy is to supplement blood units with solutions containing antioxidant molecules such as vitamin E, which has been shown to reduce ROS formation [54] , or vitamin C and N-acetylcysteine, which support antioxidant mechanisms through the ascorbate oxidation and the synthesis of new glutathione, thus preventing oxidative injury and reducing hemolysis levels during storage [55] .…”
Section: Integrative Multiomics Approaches In Human Transfusion Medicinementioning
confidence: 99%